Increased soluble interleukin-2 receptor concentration in plasma predicts a decreased cellular response to IL-2. - Gooding, R. (Nature Publishing Group, 1995)
Interleukin 2 (IL-2) immunotherapy has met with limited success in the treatment of renal cell carcinoma (RCC) and malignant melanoma (MM). However, non-responders still account for up to 80% of those patients receiving IL-2. A high concentration of soluble IL-2 receptor (sIL-2R) is commonly found in the blood of such patients. We investigated the possibility that high sIL-2R concentration pretreatment may interfere with the bioavailability of IL-2. The mean concentration of sIL-2R in plasma from patients with MM, RCC and head and neck cancer was 3378 U ml-1, 8778 U ml-1 and 764 U ml-1 respectively, compared with 1315 U ml-1 in plasma from healthy volunteers. Inclusion of plasma from patients with RCC and MM patient plasma in cytotoxic T-lymphocyte leukaemic (CTLL) cell/IL-2 assays inhibited the ability of CTLL cells to respond to IL-2, and an inverse correlation was found between the concentration of sIL-2R and the growth response of CTLL cell to IL-2 (r = -0.86, P = 0.003). Plasma with soluble IL-2R concentrations greater than 3000 U ml-1 produced a reduction in cell growth of more than 50% when included in CTLL IL-2 assays. The addition of increasing concentrations of IL-2 to cultures containing suppressive plasma failed to restore CTLL cell growth response to normal. Failure to saturate sIL-2R by exogenous IL-2 addition therefore suggests that another factor, initially present at a concentration similar to the sIL-2R concentration, is responsible for the observed effect. Determination of the suppressive effect of patient plasma as presented here may allow more effective IL-2 dosing schedules.